Pelaksanaan Pembinaan Narapidana di Rumah Tahanan Negara Klas IIB Sanggau - Iriyani, Dita; Fajrin, M; Febriany, Tri Atika (Res Judicata, 2024)
This research aims to describe and analyze the implementation of prisoner guidance at the Class IIB Sanggau State Detention Center. The study was conducted using an empirical legal research method, supported by field observations and interviews with correctional officers and inmates. The research found that the guidance program is implemented based on the Correctional System as regulated in Law No. 12 of 1995 concerning Corrections and Government Regulation No. 31 of 1999 concerning the Development and Guidance of Inmates. The implementation focuses on moral, religious, and skill development to support the prisoners’ reintegration into society. However, the study also found that human resource limitations, insufficient facilities, and lack of training programs have affected the program’s effectiveness. Overall, the guidance process has been carried out in accordance with existing regulations but requires improvement in infrastructure and management to achieve optimal results.